Profiles and Outcomes of Traumatic Glaucoma in a Tertiary Eye Hospital - Hardjasasmita, Iffa Nadifa Riza; Rifada, Raden Maula; Muslima, Patriotika (Universitas Airlangga, 2025)
Introduction: Traumatic glaucoma is one of the most significant complications from ocular injury. Identifying the cause of elevated intraocular pressure (IOP) in ocular injury, proper management, and lifelong monitoring are essential. Purpose: This study aims to describe the clinical characteristics and outcomes of patients with traumatic glaucoma in a tertiary eye hospital in Indonesia. Methods: This study employs an observational, retrospective cohort design. This study included all patients with traumatic glaucoma who came to the emergency department of Cicendo Eye Hospital, Bandung, West Java, Indonesia, from July 2023 until June 2024. Results: A total of 50 patients with secondary glaucoma due to trauma were included. The majority of patients were male (84%), with a mean age of 34.2 years. Accidents were the most common cause of injury (48%), and 60% of patients presented with severe visual impairment or blindness at initial evaluation. The most common mechanisms of elevated IOP were inflammation (34%) and mixed mechanisms (36%). Treatment was primarily involved in medical management, with 66% of patients returning for follow-up visits. During the six-month follow-up, most patients had poor visual acuity, although the mean IOP significantly decreased. Conclusions: This study emphasizes the importance of early diagnosis and treatment to prevent irreversible visual loss, as well as the need to enhance follow-up care and public health strategies to prevent ocular injuries.